Comparison of two kinetics models for estimating N mineralization affected by different quality of organic matter in Typic Hapludults - A Wijanarko; B H Purwanto (Journal of Degraded and Mining Lands Management, 2016)
N availability in the soil is determined by the rate of mineralization. N mineralization can be estimated using several models. Aim of research is  to compare of two kinetics models for estimating N mineralization affected by different inputs of  organic matter and soil fertility in Typic Hapludults. Research used completely randomized design with two factors. The first factor was land use : (1). Soil from land cultivated by cassava crops for less than 10 years, and (2). Soil from land cultivated by cassava crops for more than 30 years. The second factor was type of organic matter: (1). Groundnut biomass, (2). Maize biomass, (3). Groundnut-maize biomass, with ratio of 1:1, (4). Groundnut – maize biomass, with ratio of 2:1, (5). Groundnut – maize biomass, with ratio of 1:2, and (6). Without organic matter.  The result shows that based on the value of R2, first-order kinetics equation is more suitable to decribe N mineralization than double-pool kinetics equation because R-square value higher than double-pool kinetics and is positively correlated with N mineralization parameters (N0, k and N0.k).